(untitled) (Academicia Globe: Inderscience Research, 2024)
This article provides an analysis of the works and themes of Ghafur Ghulom, a renowned poet and writer in Uzbek children’s literature. It highlights his nurturing and paternal approach towards children, influenced by his own experiences of orphanhood. The text discusses his use of humor, philosophical depth, and emphasis on universal themes in his poetry and prose. It also explores his advocacy for the rights of orphans and his contribution to Uzbek children’s literature. The annotation serves to summarize and elucidate the key points and themes discussed in the text, providing insight into Ghafur Ghulom’s significance in the literary landscape of Uzbekistan.